2008
DOI: 10.1371/journal.pone.0003490
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Risk Locus for Multiple Sclerosis at 13q31.3 by a Pooled Genome-Wide Scan of 500,000 Single Nucleotide Polymorphisms

Abstract: Multiple sclerosis is a chronic inflammatory demyelinating disease of the central nervous system with an important genetic component and strongest association driven by the HLA genes. We performed a pooling-based genome-wide association study of 500,000 SNPs in order to find new loci associated with the disease. After applying several criteria, 320 SNPs were selected from the microarrays and individually genotyped in a first and independent Spanish Caucasian replication cohort. The 8 most significant SNPs vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
1
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(56 citation statements)
references
References 22 publications
3
49
1
3
Order By: Relevance
“…The three significant findings were simultaneously replicated in independent studies from the United Kingdom, the United States and the Nordic countries 31, 32. This opened the floodgates, with several successive studies GWAS and meta‐analysis followed in rapid succession, so that by 2011, common variants in 26 genomic loci had been associated with MS risk and independently replicated, but clearly only explained a fraction of MS risk attributable to genetic factors 33, 34, 35, 36, 37, 38, 39, 40, 41, 42. These studies collectively showed that non‐MHC MS risk alleles have modest effects on disease (odds ratios < 1.2) and that even larger sample sizes (over 10 000 cases and controls) would be needed to identify more loci 22.…”
Section: Genome‐wide Association Studiesmentioning
confidence: 91%
“…The three significant findings were simultaneously replicated in independent studies from the United Kingdom, the United States and the Nordic countries 31, 32. This opened the floodgates, with several successive studies GWAS and meta‐analysis followed in rapid succession, so that by 2011, common variants in 26 genomic loci had been associated with MS risk and independently replicated, but clearly only explained a fraction of MS risk attributable to genetic factors 33, 34, 35, 36, 37, 38, 39, 40, 41, 42. These studies collectively showed that non‐MHC MS risk alleles have modest effects on disease (odds ratios < 1.2) and that even larger sample sizes (over 10 000 cases and controls) would be needed to identify more loci 22.…”
Section: Genome‐wide Association Studiesmentioning
confidence: 91%
“…IL2R and IL7R are of particular interest because they are expressed on regulatory T cells, which have been strongly implicated in the regulation of the immune response in MS (66). Eight additional GWASs and a meta-analysis were performed and, in total, identified approximately 14 regions with genome-wide significance (77,(79)(80)(81)(82)(83)(84)(85), including several previously identified associations; among these are CD58, IL2RA, EVI5, CLEC16A, IL7RA, and TYK2 (77) and TNFRSF1A, IRF8, and CD6 (78).…”
Section: Genetics Of Msmentioning
confidence: 99%
“…Patients with a certain MS form were examined only in two GWASs, one involving patients with bout-onset MS (RRMS or SPMS) (Comabella et al 2008), and the other with PPMS (Martinelli-Boneschi et al 2012). This allowed searching for SNPs specifically involved in the given MS form development, but at the same time restricted potential sample size, thereby decreasing the power to identify associations.…”
Section: Gwas Data For Multiple Sclerosismentioning
confidence: 99%